The Critical Role of Bioturbation for Particle Dynamics, Priming Potential, and Organic C Remineralization in Marine Sediments: Local and Basin Scales - Aller, Robert C.; Cochran, J. Kirk (Frontiers in Earth Science, 2019)
Bioturbation promotes priming and total remineralization of sedimentary organic matter (Corg) in multiple ways. A primary local mode is the injection of reactive Corg from the water column, surface sediment, and mucus secretions into deposits. During feeding, burrowing, and construction activities by benthic fauna, labile substrates are brought into close association with more refractory material over a wide range of time scales, geometries, and depths, enhancing decomposition of the less reactive components (priming). One measure of these local interactions is the particle mixing coefficient, DB, which can be estimated from the averaged penetration of particle-reactive radionuclides into deposits. Patterns of DB in Long Island Sound, an estuarine system with well-defined sources of naturally-occurring radionuclides, show consistent positive correlations between DB and total inventories of 234Th (t1/2 = 24 d) and 210Pb (t1/2 = 22 yr) at local and basin scales. These correlations, maintained seasonally in the case of 234Th, demonstrate not only the penetration of plankton-derived, reactive Corg into deeper regions of deposits during bioturbation over monthly (~ 5 – 10 cm) to decadal timescales (~ 20 – 100 cm) but also the enhanced capture of labile substrates from the water column across basin scales into bioturbated patches as the intensity of reworking increases. In Long Island Sound, sedimentary Chl-a distributions and benthic nutrient regeneration (e.g., NH4+ fluxes) reflect these particle exchange processes. Basin and regional scale capture of labile substrates into bioturbated deposits can be generally demonstrated, for example, along the highly productive Cape Hatteras continental margin. Thus, total and net remineralization necessarily increase with the biogenic enhancement of the quantity of labile particulate substrate in deposits. This capture, intermixing, and close association of reactive and refractory substrates (reductant mixing), and thus the optimization of priming potential, represent important, often overlooked, pathways by which bioturbation generates biogeochemical conditions conducive to maximum efficiency of remineralization.